Bronchogenic Carcinoma after Lung Transplantation: A Case Report and Literature Review - Yeming WANG; Jingyu CHEN (Chinese Journal of Lung Cancer, 2011)
Background and objective Lung transplantation is an efficient therapeutic option for patients with end-stage pulmonary diseases, but less is known about lung cancer after lung transplantation. The aim of this study is to improve the awareness, diagnosis and treatment of bronchogenic carcinoma after lung transplantation with a case report and related literatures. Methods We reported a 65-year-old male with idiopathic pulmonary fibrosis (IPF) who underwent right lung transplantation under extracorporeal membrane oxygenation (ECMO) support in May 2007 in our hospital. The patient recovered smoothly and discharged from the hospital 46 days after the procedure with regular follow-up. Immunosuppression therapy was triple drug maintenance regimen including tacrolimus (Tac), mycophenolate mofetil (MMF) and steroids. Results Small cell lung cancer in the left lung with multiple osseous metastases was found 13 months after the lung transplantation. Symptoms were relieved a bit by administering chemotherapeutics (etoposide and cisplatin) for 4 cycles. However, the patient was succumbed to his illness within 11 months after the diagnosis of lung cancer. Conclusion Lung cancer after lung transplantation has been suggested as one of causes of late mortality with the risk factors such as chronic obstructive pulmonary disease (COPD), IPF, cigarette smoking history and immunosuppression etc. Early diagnosis and treatment are very important to improve the prognosis.